Insights into electrolyte-solvent interactions and SEI formation for sustainable sodium-ion battery operation at low temperatures - Kim, Soohwan; Mirzapure, Vinay; Atwi, Rasha; Koppisetti, Heramba V. S. R. M.; Wasnik, Kundan; Rajput, Nav Nidhi; Shelke, Manjusha; Pol, Vilas G. (Small Methods, 2025)
Sodium-ion batteries (SIBs) show promise as an alternative to lithium-ion batteries. However, they face performance challenges at ultra-low temperatures (<-40 degrees C) due to slow Na+ transfer kinetics with conventional electrolytes. This limitation restricts their use in extreme environments such as polar regions and outer space. The presented systematic study addresses this challenge by modulating and tailoring the electrolyte composition for SIBs, enabling ultra-low temperature operation down to -110 degrees C for the first time. The comprehensive molecular dynamic and density functional theory calculations combined with experimental Raman spectroscopy and nuclear magnetic resonance studies of advanced electrolytes provided a deeper mechanistic understanding of the solvation structures and their impact on electrochemical performance. By varying the solvent composition with a combination of tetrahydrofuran and 2-Methyltetrahydrofuran solvents and sodium hexafluorophosphate (NaPF6) salt, the freezing point, solubility, and Na+ solvation structure of the electrolyte is modulated and studied in detail. The extensive anion engagement in the optimized mix solvent electrolyte facilitated the formation of a stable and inorganic-rich solid electrolyte interphase layer, ensuring low overpotentials and uniform Na+ deposition, yielding superior cycling stability. As a result, the developed electrolyte enables SIBs to achieve reversible capacities of 88 mAh g(-1) at -60 degrees C and 50 mAh g(-1) at -100 degrees C. These insights may contribute to developing improved energy storage devices suitable for challenging environmental conditions.
Keywords: contact-ion pair; solid electrolyte interphase (SEI); solvation; ultra-low temperature; XPS-depth Profiling

Investigations into the nucleation dynamics of the stable Na-metal anode: revealing the role of a tin-infused carbon nanofiber interlayer - Wasnik, Kundan; Yadav, Poonam; Ahuja, Manuj; Mirzapure, Vinay; Johari, Priya; Shelke, Manjusha V. (ACS Applied Materials & Interfaces, 2025)
Fundamental understanding and controlling of sodium nucleation are essential for enhancing the performance, safety, and longevity of sodium metal batteries, which is not yet clearly understood in the case of sodium metal batteries. The present study showcases how a modification in the host material influences nucleation kinetics. Current-time transient studies on copper, carbon nanofiber, and tin-embedded carbon nanofiber interlayers employing the Scharifker-Hills model elucidate the mode of nucleation. This work tries to delve deep and presents a case study on how a tin-based interlayer can not only minimize the barrier for sodium nucleation but also direct the sequential progressive and instantaneous nucleation of sodium metal while reducing the overpotential substantially, resulting in crystalline, uniform Na-metal deposition. Further, to account for the complex dynamics of solid electrolyte interphase (SEI) formation distinctly associated with alkali metal deposition, the SEI-fracture model has been included, and the quantification of electrochemical nucleation parameters is obtained. The results provide important insights into the sodium nucleation mechanism, paving the way to counter dendrite formation and SEI dissolution issues of the Na-metal anode.
Keywords: overpotential; progressiveand instantaneous nucleation; Scharifker-Hills model; SEI-fracture model; tin interlayer